Behavioural Thermoregulation of Flowers via Petal Movement - Matthew H. Koski; Jacob M. Heiling; Jennifer S. Apland (Ecology Letters, 2024)
Widely documented in animals, behavioural thermoregulation mitigates negative impacts of climate change. Plants experience especially strong thermal variability but evidence for plant behavioural thermoregulation is limited. Along a montane elevation gradient, Argentina anserina flowers warm more in alpine populations than at lower elevation. We linked floral temperature with phenotypes to identify warming mechanisms and documented petal movement and pollinator visitation using time‐lapse cameras. High elevation flowers were more cupped, focused light deeper within flowers and were more responsive to air temperature than low; cupping when cold and flattening when warm. At high elevation, a 20° increase in petal angle resulted in a 0.46°C increase in warming. Warming increased pollinator visitation, especially under cooler high elevation temperatures. A plasticity study revealed constitutive elevational differences in petal cupping and stronger temperature‐induced floral plasticity in high elevation populations. Thus, plant populations have evolved different behavioural responses to temperature driving differences in thermoregulatory capacity.

Correction to: Functional redundant soil fauna and microbial groups and processes were fairly resistant to drought in an agroecosystem - A. Watzinger; J. Prommer; A. Spiridon; W. Kisielinska; R. Hood-Nowotny; S. Leitner; W. Wanek; C. Resch; M. Heiling; E. Murer; H. Formayer; A. Wawra; et al. (Biology and Fertility of Soils, 2023)

Functional redundant soil fauna and microbial groups and processes were fairly resistant to drought in an agroecosystem - A. Watzinger; J. Prommer; A. Spiridon; W. Kisielinska; R. Hood-Nowotny; S. Leitner; W. Wanek; C. Resch; M. Heiling; E. Murer; H. Formayer; A. Wawra; et al. (Biology and Fertility of Soils, 2023)
Climate change scenarios predict more frequent and intense drought periods for 2071 to 2100 for many regions of the world including Austria. Current and predicted lower precipitation scenarios were simulated at a lysimeter station containing a fertile and less fertile agricultural soil for 9 years. 13 C and 15 N-labeled green manure was added in year 8 with the aim to analyze how the predicted precipitation regime affects soil fauna and microbial groups and consequently nitrogen (N) and carbon (C) cycling. Among the investigated mesofauna (collembola and oribatida), the abundance and biodiversity of oribatida was significantly reduced by drought, possibly because they mainly represent K-strategist species with low mobility and consequently the need to adapt to long-term adverse environmental conditions. Microbial community composition and microbial biomass, investigated by phospholipid fatty acid (PLFA) analysis, was indistinguishable between the current and the predicted precipitation scenarios. Nonetheless, soil 13 C-CO 2 emissions and soil water 15 N-NO 3 data revealed decelerated mineralization of green manure under reduced precipitation in the first 2 weeks, but no effects were observed on soil C sequestration or on 13 C incorporation into microbial PLFAs in the following 1.2 years. We found that over a 1-year time period, decomposition was rather driven by plant residue availability than water limitation of microorganisms in the investigated agroecosystem. In contrast, N 2 O emissions were significantly reduced under drought, and green manure derived 15 N accumulated in the soil under drought, which might necessitate the adjustment of future fertilization regimes. The impacts of reduced precipitation and drought were less pronounced in the more fertile agricultural soil, due to its greater buffering capacity in terms of water storage and organic matter and nutrient availability.

Evidence for UV-based sensory exploitation in Australian but not European crab spiders - M. E. Herberstein; A. M. Heiling; K. Cheng (Evolutionary Ecology, 2009)

The aggregating behaviour of Argiope radon, with special reference to web decorations - Dinesh Rao; Malcolm Webster; Astrid M. Heiling; Matthew J. Bruce; Marie E. Herberstein (Journal of Ethology, 2009)

Why do nocturnal orb-web spiders (Araneidae) search for light? - Astrid M. Heiling (Behavioral Ecology and Sociobiology, 1999)